(untitled) (Panauti Journal, 2024)
Remittance is becoming prominent source of family income in Nepal. This study thus, analyzes effect of remittance on household welfare. We adopted cross-sectional study design to collect data from 777 randomly selected respondents residing in Chautara Sngachwokgadhi (Mountain region), Galkot (Hill) and Mithila (Tarai) municipalities of Nepal. We used a reliable questionnaire tool having 0.8 cronbach alpha, and we visited the respondents from 6th June- 18th October 2022. The study found that the remittance has positive effect on household welfare of the remittance recipient households. They have good access to households, educational, financial and health facilities. Utilization of remittance helped to increase family income, helped to improve family economic situation and livelihood, helped to reduce family poverty and social exclusion, helped to create self-employment/employment and help to upgrade rural economy in the study area. However, remittance has failed to increase agriculture production and distributions (domestic household hazard) and also failed to increase entrepreneurship development in the local levels. Therefore, the empirical findings of the study can be a reference for developing evidence based policy to the concerned state actor and non-state stakeholders for minimizing public moral hazard and domestic household hazards caused by remittance.